PRK vs LASEK vs Epi-LASIK: A comparison of corneal haze, postoperative pain and visual recovery in moderate to high myopia - Reilly, CD; Panday, V; Lazos, V; Mittelstaedt, BR (Nepalese Journal of Ophthalmology, 2010)
Introduction: The field of refractive surgery continues to evolve amid continued concerns as to which surgical technique minimizes the risk of inducing ectasia. Purpose: To compare clinical outcomes between PRK, LASEK and Epi-LASIK in moderately to highly myopic eyes (-4.00 D to -8.00 D). Materials and methods: A retrospective chart review of 100 PRK eyes, 100 LASEK eyes (with alcohol) and 97 Epi-LASIK eyes was performed. Post-operative pain, uncorrected visual acuity, and corneal haze data was recorded and analyzed at post-op days 1, 4 and 7 and at post-op months 1, 3, 6 and 12. Results: In all groups surgical corrections ranged from -4.00 D to -8.00 D. There was less pain associated with the epi-LASIK procedure especially early (post-op days 1 and 4). Visual recovery was superior within the PRK group during the first post-operative week but by post-op week 4 all three were equal. Haze scores were similar but a trend for less haze was demonstrated with epi-LASIK at 6 and 12 months. Conclusion: Epi-LASIK has a slight advantage over PRK and LASEK early on in the post-op course with regards to pain. Visual recovery is similar by 4 weeks and is better with PRK early. In addition, epi-LASIK trends toward less significant haze. Keywords: LASIK; epi-LASIK; LASEK; PRK; haze DOI: 10.3126/nepjoph.v2i2.3715 Nep J Oph 2010;2(2) 97-104